Academics' experience of copyright: A case study of teaching at the University of Greenwich. Issue 6 (2nd September 2019) - Chauhan, Vikee; Willett, Peter
Abstract : Purpose: The purpose of this paper is to obtain a snapshot of attitudes and comprehension of the University of Greenwich (UoG) academics towards copyright and the impact of same on their teaching, complementing this with a survey of the experience of academic librarians (ALs) throughout the UK when dealing with faculty and copyright. Design/methodology/approach: Two questionnaires were created and circulated to capture information from two sampled groups: the UoG academic staff and UK-wide ALs. A total of 55 responses were received to the questionnaire distributed to the former, and 83 responses were received to the questionnaire distributed to the latter. Findings: The majority of the UoG academics believed they possessed a fair, or better than fair, understanding of copyright, with numerous respondents self-taught on the subject. Nevertheless, a significant number thought they might have broken copyright when teaching, while also revealing the belief that copyright was a limitation on their teaching. The AL survey suggested an average comprehension of copyright among academics, while noting that some of the latter felt a degree of antipathy towards copyright. Originality/value: Although focused on a single institution, this study implies that copyright instruction for academic staff needs to be substantially improved, and it suggests the need for greater visibility of training programmes.